Genetic analysis of food preferences in the population of Ukraine - Тимошина, І. А.; Чечуй, О. Ф.; Павиченко, О. В.; Філіпцова, О. В. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
A genetic analysis of food preferences based on Falconer approach was conducted in Ukraine for the first time. The questionnaires on food preferences were filled by 291 “parent–offspring” pairs (including 19 “father–son” pairs, 54 “mother–son” pairs, 34 “father–daughter” pairs and 184 “mother–daughter” pairs), 84 sibling pairs (including 7 male sibling pairs, 36 female sibling pairs and 41 opposite sex sibling pairs) and 70 marital couples. A moderate heritability of food preferences for healthy food (the first vegetable dishes) – 50%, and a high heritability for protein foods (meat) – 88%, fruits – 92%, salty food – 76%, as well as sweets and fast food – about 100% were shown.